VD_FINDINFO HC / 2011 / 145 vom 21. März 2011 - VD Tribunal cantonal (2011)
EXPULSION DE LOCATAIRE, SOUS-LOCATION, LOGEMENT DE LA FAMILLE, EXÉCUTION FORCÉE | 309 let. a CPC (CH), 319 let. a CPC (CH), 320 let. a CPC (CH), 320 let. b CPC (CH), 339 al. 2 CPC (CH), 341 CPC (CH), 346 CPC (CH)